A Retrospective Case-Control Study of Lipid Profiles in Carcinoma Breast in Comparison with Normal Controls - Yalagachin, Gurushantappa; S, Praveena (Medical Journal of Shree Birendra Hospital, 2021)
Introduction: Breast cancer is the second most common cancer in the world. One of the reasons for its increasing prevalence, especially in younger women has been attributed to lifestyle changes. All these factors also have a strong association with lipid metabolism. More evidence is coming forward to emphasise the protective effect of lifestyle modification to lower lipid levels and thus decreasing the risk of breast cancer. Methods: It is a retrospective, case control study. The patients with carcinoma breast and normal controls were taken as subjects. The data for this study includes clinical profile and lipid profile measured in early morning fasting sample of the subjects. The patients of carcinoma breast, normal control aged > 18 years were included, while patients with diabetes, thyroid disorders, on treatment for hyper-lipidaemia, dieting or anorexic, pregnant patients were excluded. Results: There was no statistically significant differences in age (p = 0.920) and BMI (p = 0.137) between study and normal control group. Total Cholesterol (TC) and Triglycerides (TG) levels were significantly elevated (p = 0.009 and 0.000 respectively) in carcinoma breast group compared to normal controls, however no significant differences (p > 0.05) observed in the levels of HDL-C, LDL-C. Conclusions: There is a significant alteration in lipid metabolism in carcinoma breast patients in comparison to normal controls.